Pseudo-rheumatic manifestations of limping: Camptodactyly–arthropathy–coxa vara–pericarditis syndrome: Single case report and review of the literature - Maniscalco, Valerio; Pizzetti, Camilla; Marrani, Edoardo; Perrone, Anna; Maccora, Ilaria; Pagnini, Ilaria; Artuso, Rosangela; Simonini, Gabriele; Mastrolia, Maria Vincenza (Frontiers in Pediatrics, 2022)
Camptodactyly–arthropathy–coxa vara–pericarditis (CACP) syndrome is a rare genetic disease characterized by tetrad camptodactyly, noninflammatory arthropathy, coxa vara deformity, and pericardial effusion. Arthropathy typically affects large joints and presents with joint swelling in the absence of other signs of inflammation. We described the case of a girl affected by CACP syndrome caused by a novel compound heterozygous variant in proteoglycan 4 gene (c.2831_2832insT; c.3892C > T) and associated with temporomandibular involvement. The patient received treatment with intra-articular hyaluronic acid injections, which presented rapid but transient improvements of pain and range of motion. A literature review of previously reported CACP patients has been performed. Of the patients. 69.2% (101 out of 146) were Middle Eastern, and 65.7% (96) were consanguineous. The median age of onset was 24 months (interquartile range of 12–36 months), and median age of diagnosis was 96 months (interquartile range of 48–156 months). Arthropathy was always present, mainly involving hips (95.2%), knees (92.4%), wrists (87.7%), elbows (79.5%), and ankles (57.5%). Camptodactyly and pericardial effusion were described, respectively, in 97.3% (142) and 15.1% (22) of patients. The main radiological findings were coxa vara (95.2%), femoral changes (64.4%), intraosseus cysts (14.4%), and bone erosion (5%). Of the patients, 32.9% (48) had received a previous juvenile idiopathic arthritis diagnosis. CACP syndrome can be easily misdiagnosed with juvenile idiopathic arthritis. A prolonged lack of response to immunosuppressive therapy associated with typical clinical and radiological features should prompt consideration of this rare syndrome.